Towards applications of graded Paraparticle algebras - Kanakoglou, K.; Hererra-Aguilar, A. (HNPS Advances in Nuclear Physics, 2019)
An outline is sketched, of applications of the ideas and the mathematical methods presented at the 19th symposium of the Hnps in Thessaloniki, May 2010